Pengaruh Solvabilitas dan Likuiditas Terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi - Mayuari Ramadhanti; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to test the effect of solvability and liquidity on firm value with financial performance as a mediating variable. The population in this research are property, real estate and building construction sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The number of research samples used is 40 companies with purposive sampling technique and the number of observations of this research data was 160. The data analysis method used in this study is multiple linear regression and path analysis. The results show indicate that liquidity has no effect on financial performance and solvability has no effect on firm value. However, solvability affects financial performance, liquidity and financial performance effects firm value. Financial performance does not mediate solvability and liquidity on firm value.